2017
DOI: 10.3892/etm.2017.4057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vacuum sealing drainage on the expression of VEGF and miRNA-17-5p in seawater-immersed blast-injury wounds

Abstract: Abstract. The aim of the present study was to compare and observe the expression levels of vascular endothelial growth factor (VEGF) and miRNA-17-5p during the treatment of seawater-immersed blast-injury wounds (SIBIW) under different conditions of vacuum sealing drainage (VSD), and to identify the optimized range of VSD treatment and partially explain its mechanisms. The bilateral hips and scapulae of experimental pigs (weight, 25-30 kg) were subjected to blast-injury wounds, followed by the seawater immersio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It is clinically recommended to perform active therapies for chronic infectious wounds, such as dressing change treatment and vacuum sealing drainage 13 . However, insufficient knowledge and poor psychological state of patients may cause poor therapeutic effects 14 - 16 . Therefore, it is crucial to perform reasonable nursing interventions for such patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is clinically recommended to perform active therapies for chronic infectious wounds, such as dressing change treatment and vacuum sealing drainage 13 . However, insufficient knowledge and poor psychological state of patients may cause poor therapeutic effects 14 - 16 . Therefore, it is crucial to perform reasonable nursing interventions for such patients.…”
Section: Discussionmentioning
confidence: 99%
“…It can also promote the production and release of growth‐promoting factors and accelerate the growth of granulation tissue. 31 , 32 , 33 In recent years, autologous PRP has been gradually used in the treatment of DFU and has achieved good results. 34 Autologous platelet‐rich gel belongs to the natural biological preparation of platelets, which is derived from the patient's blood and therefore has the advantage of low immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Directed VSD could effectively reduce wound tissue oedema, improve wound microcirculation, and remove harmful inflammatory molecules in time. It can also promote the production and release of growth‐promoting factors and accelerate the growth of granulation tissue 31‐33 . In recent years, autologous PRP has been gradually used in the treatment of DFU and has achieved good results 34 .…”
Section: Discussionmentioning
confidence: 99%
“…First, we established a full-thickness skin defect model and immersed the wound completely in artificial seawater. During the healing period on days 7 and 14, the reepithelialization and closure of the seawater-immersed wounds were slower than what was observed in control wounds, demonstrating that seawater impedes wound healing [21]. Subsequently, hADSCs or an equal volume of DMEM were injected around the wounds, and it was observed that wounds with the hADSC injection had a better closure efficiency.…”
Section: The Effect Of Hadscs On the Treatment Of Seawater-mentioning
confidence: 96%